Sexually dimorphic production of interleukin‐6 in respiratory disease. Issue 11 (30th May 2020) - Reddy, Karosham D.; Rutting, Sandra; Tonga, Katrina; Xenaki, Dikaia; Simpson, Jodie L.; McDonald, Vanessa M.; Plit, Marshall; Malouf, Monique; Zakarya, Razia; Oliver, Brian G.
Abstract: Diverging susceptibility and severity in respiratory diseases is prevalent between males and females. Sex hormones have inconclusively been attributed as the cause of these differences, however, strong evidence exists promoting genetic factors leading to sexual dimorphism. As such, we investigate differential proinflammatory cytokine (interleukin (IL)‐6 and CXCL8) release from TNF‐α stimulated primary human lung fibroblasts in vitro. We present, for the first time, in vitro evidence supporting clinical findings of differential production of IL‐6 between males and females across various respiratory diseases. IL‐6 was found to be produced approximately two times more from fibroblasts derived from females compared to males. As such we demonstrate sexual dimorphism in cytokine production of IL‐6 outside the context of biological factors in the human body. As such, our data highlight that differences exist between males and females in the absence of sex hormones. We, for the first time, demonstrate inherent in vitro differences exist between males and females in pulmonary fibroblasts. Abstract : Current understanding of the sex differences in respiratory disease is incomplete. We identify for the first time, a difference in immunological response between men and women with respiratory disease diagnosis. Hence, we show a differential response exists outside the context of hormones.